Assessing the effectiveness of bridge grate and pipe cattle guard designed to mitigate ocelot road mortality on Texas state highway - Maharjan, Rupesh; Young, John H.; Ryer, Kevin; Rahman, Md Saydur; Kline, Richard J. (Frontiers in Ecology and Evolution, 2025)
The mitigated and fenced section of State Highway 100, extending from Laguna Vista to Los Fresnos, includes five wildlife crossing structures and 16 modified cattle guards (also called wildlife guards) installed to mitigate ocelot road mortality. Bridge grate and pipe wildlife guards were deployed at vehicle entries, and we evaluated their effectiveness in preventing meso-carnivores and ungulates from entering the roadway through the fence gaps from April 2020 to 2024. Wildlife guards collectively were >82% effective in repelling ungulate attempts to enter the roadway, while only 16.64% of meso-carnivore attempts were repelled. The pipe wildlife guard (PWG) design repelled 86.79% of ungulates and 18.83% of meso-carnivore attempts to enter the roadway. In comparison, the bridge grate wildlife guard (BGWG) design repelled 81.51% of ungulates and 15.81% of meso-carnivores. Our results indicate that PWG and BGWG effectively prevented ungulates from entering the roadway through fence gaps. Although both PWG and BGWG had low repulsion rates for meso-carnivores, PWG was found to be more effective at preventing meso-carnivores from entering the roadway.